A Review of the Literature Regarding Sleep and Cardiometabolic Disease in African Descent Populations - Whitesell, Peter L.; Obi, Jennifer; Tamanna, Nuri S.; Sumner, Anne E. (Frontiers in Endocrinology, 2018)
In the 21st century, African descent populations on both the continent of Africa and throughout the world are experiencing a high rate of both sleep disturbances and cardiometabolic diseases. The most common sleep disturbances are reduced sleep duration, insomnia, disordered circadian rhythm, and obstructive sleep apnea. Cardiometabolic diseases include hypertension, coronary artery disease, diabetes, hyperlipidemia, and the metabolic syndrome. This review seeks to call attention to new insights regarding the impact of sleep disturbance on cardiometabolic risk factors and outcomes and then apply these concepts to African descent populations, a relatively understudied population. Initial data suggest disparities in sleep quality may have an important role in current and emerging patterns of cardiometabolic disease for African descent populations both in the United States and abroad.